2005
DOI: 10.1001/jama.294.5.563
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Therapy for the Prevention of Suicide Attempts

Abstract: Cognitive therapy was effective in preventing suicide attempts for adults who recently attempted suicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
661
4
30

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 936 publications
(715 citation statements)
references
References 39 publications
20
661
4
30
Order By: Relevance
“…Cognitive-behavioural therapy for DSH seems to be an effective intervention for DSH as shown in previous studies (Brown et al, 2005;Palmer et al, 2006;Slee et al, 2008a). Despite the demonstrated effi cacy of CBT for DSH, very little is known about the mediating variables that lead to the reduction of DSH.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Cognitive-behavioural therapy for DSH seems to be an effective intervention for DSH as shown in previous studies (Brown et al, 2005;Palmer et al, 2006;Slee et al, 2008a). Despite the demonstrated effi cacy of CBT for DSH, very little is known about the mediating variables that lead to the reduction of DSH.…”
Section: Discussionmentioning
confidence: 53%
“…An RCT of brief CBT versus usual care showed that brief CBT was of limited effi cacy in reducing DSH (Tyrer et al, 2003), whereas an RCT of cognitive therapy (CT) reported favourable outcomes with regard to the number of suicide attempts, depression severity and thoughts of hopelessness (Brown et al, 2005). The BOSCOT trial evaluated the clinical effectiveness and cost-effectiveness of CBT for suicidal patients with borderline personality disorder Palmer et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For information on the effectiveness of the remaining interventions not covered in this report the reader is instead referred to our review in the Cochrane Library. 13 A total of 29 trials were therefore included in the present review (Figure 1; Supplementary Document SD3), comprising 18 trials of cognitive behavioural-based psychotherapy (CBT), [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] three trials of dialectical behaviour therapy (DBT), [36][37][38] and four trials each of case management [39][40][41][42] and postcards. [43][44][45][46] (Insert Figure 1 about here)…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Data on the proportion of patients repeating self-harm by the end of treatment was only available for one trial, 27 in which there was no apparent effect (23/171 vs. 27/142, OR 0·66, 95% CI 0·36 to 1·21, N=313). However, CBT-based therapy was associated with fewer participants repeating self-harm at the six month (OR 0·54, 95% CI 0·34 to 0·85, N=1,317; Figure 2) and 12 month follow-up assessments (OR 0·80, 95% CI 0·65 to 0·98, N=2,232; Figure 2).…”
Section: Cognitive Behavioural-based Psychotherapy Versus Treatment Amentioning
confidence: 99%
“…This report focuses on the acceptability of MI-SI for psychiatrically hospitalized veterans who are thinking about suicide, and its potential for reducing the severity of suicidal ideation. Suicidal ideation was chosen as the suicide-related outcome because it is a necessary precursor to suicidal behavior (Conner, McCloskey, & Duberstein, 2008;Kessler, Borges, & Walters, 1999), is sensitive to change (Beck, Kovacs, & Weissman, 1979;Linehan, Armstrong, Suarez, & Allmon, 1991), and the large samples and follow-up periods needed to use suicide attempts as an outcome are beyond the scope of preliminary studies (Brown et al, 2005;Clarkin, Levy, Lenzenweger, & Kernberg, 2007).…”
mentioning
confidence: 99%